Iridium‐Catalyzed Arylative Cyclization of Alkynones by 1, 4‐Iridium Migration. (19th May 2014) - Partridge, Benjamin M.; Solana González, Jorge; Lam, Hon Wai
Abstract: 1, 4‐Metal migrations enable the remote functionalization of CH bonds, and have been utilized in a wide variety of valuable synthetic methods. The vast majority of existing examples involve the 1, 4‐migration of palladium or rhodium. Herein, the stereoselective synthesis of complex polycycles by the iridium‐catalyzed arylative cyclization of alkynones with arylboronic acids is described. To our knowledge, these reactions involve the first reported examples of 1, 4‐iridium migration. Abstract : Wanderung zum Iridium : Iridium‐Katalyse ermöglicht die arylierende Cyclisierung von Alkinonen mit Arylboronsäuren zu komplexen Polycyclen mit hohen Stereoselektivitäten. Diese Reaktionen sind die ersten Beispiele für eine 1, 4‐Iridium‐Migration.